(untitled) (Environment & Health, 2021)
The aim of the study is to determine the mechanisms for the formation and progressivity of chronic diffuse liver diseases in victims of the Chornobyl Nuclear Power Plant accident with the development of a diagnosis criteria for fibrous changes in this pathology. The materials were the results of examination and treatment in the clinic of the State Institution "NRCRM of the NAMS of Ukraine" of victims of the Chornobyl Nuclear Power Plant accident, 57 of which, according to the criteria for switching on and off, were assigned to the main group. The research methods were: general clinical examination, instrumental studies (ultrasound diagnostics of abdominal organs), biochemical, medical statistics, analytical. According to the results of the study, it was proved that in the victims of the Chornobyl Nuclear Power Plant accident, the main liver pathology was non-alcoholic fatty liver disease. It has been shown that in patients affected by the Chernobyl disaster, NAFLD develops a pronounced violation of fat metabolism with a reliable decrease in cholesterol and beta-lipoproteins in cirrhosis – a sign of a long-term course of the disease, accompanied not only by the development of fibrosis, but also by a fatty rebirth of liver tissue with low cholesterol and beta-lipoproteins; this can be considered a marker of cirrhosis in the Chornobyl accident clean-up personnel with NAFLD.